Produkty ekologiczne na niemieckim rynku żywności - Pilarski, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
At nowadays market, the assortment of organic products responds to nearly all consumers' needs, and offers various equivalents of traditional products. The turnover of organic food increases annually. In 2005 the circulation was 4 billion euro, which was 2.4% of all circulations of food in Germany. The highest sale income of organic products gained traditional detailed shops. To increase their circulations, sale of the other forms of sales decreases. Weil developed market is somehow an effect of expanded market infrastructure. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 296-303